Preclinical Studies of Chemotherapy Using Histone Deacetylase Inhibitors in Endometrial Cancer - Noriyuki Takai; Hisashi Narahara (Obstetrics and Gynecology International)
Because epigenetic alterations are believed to be involved in the repression of tumor suppressor genes and promotion of tumorigenesis in endometrial cancers, novel compounds endowed with a histone deacetylase (HDAC) inhibitory activity are an attractive therapeutic approach. In this review, we discuss the biologic and therapeutic effects of HDAC inhibitors (HDACIs) in treating endometrial cancer. HDACIs were able to mediate inhibition of cell growth, cell cycle arrest, apoptosis, and the expression of genes related to the malignant phenotype in a variety of endometrial cancer cell lines. Furthermore, HDACIs were able to induce the accumulation of acetylated histones in the chromatin of the p21WAF1 gene in human endometrial carcinoma cells. In xenograft models, some HDACIs have demonstrated antitumor activity with only few side effects. In this review, we discuss the biologic and therapeutic effects of HDACIs in treating endometrial cancer, with a special focus on preclinical studies.